2021
DOI: 10.1038/s41598-021-97035-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the best monochromatic energy level in dual energy spectral imaging for coronary stents after percutaneous coronary intervention

Abstract: In this study, the optimal monochromatic energy level in dual-energy spectral CT required for imaging coronary stents after percutaneous coronary intervention (PCI) was explored. Thirty-five consecutive patients after PCI were examined using the dual-energy spectral CT imaging mode. The original images were reconstructed at 40–140 keV (10-keV interval) monochromatic levels. The in-stent and out-stent CT values at each monochromatic level were measured to calculate the signal-to-noise ratio(SNR) and contrast-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The ideal type of image, including the specific energy level of VMI, depends on several factors, including the scanner technology, body part, the specific clinical task, and noise. 25,[31][32][33] Our study showed that 50 keV images are superior to 120 kV images for overall image quality, vascular enhancement, and coronary artery sharpness with mild increased noise. Knowledge of the preferred image is essential to simplify the workflow, both for the scanning technologist and interpreting cardiac imager.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The ideal type of image, including the specific energy level of VMI, depends on several factors, including the scanner technology, body part, the specific clinical task, and noise. 25,[31][32][33] Our study showed that 50 keV images are superior to 120 kV images for overall image quality, vascular enhancement, and coronary artery sharpness with mild increased noise. Knowledge of the preferred image is essential to simplify the workflow, both for the scanning technologist and interpreting cardiac imager.…”
Section: Discussionmentioning
confidence: 64%
“…With the availability of ME capabilities on PCD-CT, additional image sets can be generated, including full spectrum (120 kV) and VMIs. The ideal type of image, including the specific energy level of VMI, depends on several factors, including the scanner technology, body part, the specific clinical task, and noise 25,31–33 . Our study showed that 50 keV images are superior to 120 kV images for overall image quality, vascular enhancement, and coronary artery sharpness with mild increased noise.…”
Section: Discussionmentioning
confidence: 71%
“…The value of VMI for CCTA has been proven for various dual-energy CT and PCCT scanners [ [13] , [14] , [15] ]. Few studies have looked at the impact of VMI and optimal keV level in the presence of cardiac stents [ 16 , 17 ]. However, these studies were carried out with dual energy CT systems using energy integrating detectors, incapable of generating comparable UHR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been some studies on MARs technology for artifact reduction in metal implants such as hip prostheses and pedicle screws, but only a few studies have examined the use of MARs in TKA (13,15,16). The purpose of this study was to explore the feasibility and effectiveness of the MARs reconstruction algorithm in reducing metal artifacts of knee prostheses and to explore the optimal monochromatic level of the VMS images for artifact reduction to provide high-quality images and reliable diagnosis for patients after TKA.…”
Section: Introductionmentioning
confidence: 99%